KORELASI PENGUASAAN KOSAKATA BIDANG LINGKUNGAN DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 3 PADANG PANJANG - Nilawati, Debby Ayu; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This article was written to describe the relation the mastery of the vocabulary environment to the skill writting the text of the exposition  students in class VIII padang Panjang Junior High School 3. This type of research is quantitative with descriptive method and correlational design. The sample in this study amounted to 44 people. The data of this research is score the mastery of the vocabulary environment the exposition text and skill test result writting the text of exposition. The data were gotten through an objective test intended to measure the students the mastery of the vocabulary environment and performance test intended to measure the students skills of writting the text of exposition. Based on data analysis, the following three things are obtained. First, skill of writing the exposition text students in class VIII padang Panjang Junior High School 3 is in good qualification (81,91). Second, the skill the mastery of the vocabulary environment the exposition text of students in class VIII padang Panjang Junior High School 3 is in good qualification (82,05). Third, there was a significant corelation between the students the mastery of the vocabulary environment of exposition text with the skills of writing the exposition text of strudent of class VIII padang Panjang Junior High School 3 in which the significance level 95% with the degrees of freedom n-1 (dk = n-1). Based on this, it was concluded that writing an exposition text requers the mastery of environmental vocabulary. Kata kunci: Korelasi, Kosakata, Menulis, dan Teks Eksposisi